PERINGATAN ALLAH DALAM AL-QURAN SURAH AL BALAD AYAT 1-10 - Aldi Maulana Ong; Arjuna Barkah Firdaus Nasution (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This article tries to elaborate the meaning of al-Balad in the Qur'an. The Term al-Balad is one of the vocabulary in the Qur'an which is important to exegete its meaning. Al-Balad, which is often translated as country, state, land, city, region and its many mentions in the Qur'an shows that the existence of balad for a society is very important for the continuity of life and prosperity of a society. This article is library research with references to the mufradat dictionary of the Qur'an Mu'jam Mufahras li Ma'ani al-Qur'an and commentary books of Qur’an such as Al-Tafsir al- Bayani li al-Qur'an al-Karim. Whereas the data analysis technique used is the content analysis technique. This study resulted in that the term al-Balad and its derivations are scattered in the Qur'an nineteen times, both in the Mecca and Medina periods. There are three meanings of the use of al-balad, namely the land of Mecca, a country in general that can be characterized as good or bad and, in the plural, which means country.